Effect Subtitution Duck Manure Fermentation for Feed Juvenile Catfish (Clarias sp.) - Baruna Kusuma; Esna Dili Novianto (Journal of Livestock Science and Production, 2018)
Pellet in the catfish can replaceable with fermented duck manure. The effect of substitute pellet feed juvenile catfish with fermented duck manure was investigated. Fermentation of duck manure with traditional food starter. Traditional food starter is tape yeast containing of genus Aspergilius, Saccharomyces, Candida, Hansenulla, dan bakteri Acetobacter. Catfish diets studies with 5% pellet/fish/day (W/W/day). Four treatment replacement in the total weight diets was substitute by fermented duck manure 45% (A), 30% (B), 15% (C) and 0% (D) levels formulated and feed to catfish juvenile (weight 2,75±0,05 g) for 30 day on controlled aquaria. Results from studies found that the best diet formulation can provide catfish juvenile growth response was diet C and D. Duck manure can reaplace feed juvenile catfish with duck manure fermentation until 15% from catfish diets.Key words: fermented duck manure, substitute pellet, catfish juvenile growth